The Manipulation of Online Self-Presentation - Attrill, A. author. aut Link
XIV, 128 p.
Keywords: This book explores psychological theories around the ways in which people present themselves online. The role of dispositional and situational factors along with the motivations that drive self-presentation across diverse Internet arenas are considered.